A new approach for selecting the switching states of SVPWM algorithm in multilevel inverter - Tuncer, S.; Tatar, Y. (Wiley, 2007)
This paper presents a fast and real-time space vector pulse width modulation (SVPWM) algorithm for multilevel inverters. A min.-max. method for selecting switching states is proposed for SVPWM algorithm. With the proposed method, the minimum switching commutation transition of between the triangles on the space vector diagram of the reference voltage vector is provided. The proposed SVPWM algorithm is also rather suitable for all values of linear modulation range and provides simplicity and applicability. Using this SVPWM algorithm, three-phase voltages have been obtained from a five-level cascade inverter. These voltages are applied to a three-phase ac motor. The simulation results are verified by the experimental results. Copyright (C) 2006 John Wiley & Sons, Ltd.
Keywords: multilevel inverter; space vector PWM; selecting the switching states